Avaliação clínica e parasitológica de animais inoculados com vacinas inativadas de Anaplasma marginale e desafiados experimentalmente - Pedro Veloso Facury Lasmar (2010)
In the present work, inactivated vaccines of Anaplasma marginale were valued (vaccine containing 3 x 109 corpuscles of Anaplasma marginale + oil adjuvante, vaccine containing 3 x 109 corpuscles of Anaplasma marginale + culture supernatant and saponin as an adjuvant and vaccinates with culture supernatant + saponin together with a control group (saline solution + oil solution) in 20 calves (HPB) with six months of age, in front of experimental challenge with 3 x 105 corpuscles of Anaplasma marginale sample UFMG2 (sample without appendix,thought of rise pathogenicity). The method used for the evaluation of these vaccines they were soroconvesion, incubation period (PI), patent period (PP) and period of convalescence (PC). During these periods the next clinical parameters were valued: cardiac and respiratory frequencies, retal temperature, rounded volume and parasitemia (smear of blood and flow cytometry), as well as the correlation between these variables. There did not take place significant difference (p> 0,05) between the groups regarding the PI, PP and PC as well as in the clinical parameters.